Development of an E-Module on Occupational Safety, Occupational Health, and Environmental Protection Topics for Android-Based Information and Communication Technology Vocational Competency - Pangestika, Senjany Julaeshy; Supraptono, Eko; Kusumastuti, Adhi (Journal of Vocational and Career Education, 2023)
The learning achievement in the field of safety, occupational health, and environmental protection (K3LH) material is suboptimal, even though in the industrial sector, it serves as the fundamental knowledge for establishing a healthy and safe working environment. Therefore, the objective of this research is to analyze the procedure for developing an Android-based K3LH e-module, assess the feasibility of the e-modules, evaluate their practicality, and ascertain their effectiveness by measuring student competency scores. The research methodology employs the ADDIE (Analysis, Design, Development, Implementation, Evaluation) approach model, involving 37 respondents who are 10th-grade students specializing in Information and Communication Technology Competency at SMK Ma'arif NU Paguyangan. The outcomes revealed that the e-module demonstrated a high level of feasibility, as determined through expert validation, comprehensive features, and user-friendly design. The module's practicality was also substantiated by user data, indicating a high level of practicality. Furthermore, the increased competency results indicated the effectiveness of the presented modules. In conclusion, this research establishes that the developed e-module effectively enhances student competence in HSE (Health, Safety, and Environmental) material. It offers several advantages, including comprehensive features, the inclusion of mini-games that pique student interest in module utilization, and easy accessibility, which allows for more flexible exploration of the material.